Changes of Peripheral Th17 Cells Subset in Overweight and Obese Children After Body Weight Reduction - Artemniak-Wojtowicz, Dorota; Kucharska, Anna M.; Stelmaszczyk-Emmel, Anna; Majcher, Anna; Pyrżak, Beata (Frontiers in Endocrinology, 2022)
Background Obesity has been a growing problem in young patients leading to serious metabolic complications. There are many studies supporting the idea, that obesity should be considered as a chronic inflammation closely associated with immune system alterations. Th17 subpopulation is strongly involved in this process. The aim of our study was to evaluate circulating Th17 cells in overweight and obese children and explore the relationships between Th17 subset and metabolic parameters. Methods We evaluated peripheral Th17 cells in fresh peripheral blood samples from 27 overweight and obese and 15 normal-weight children. Th17 cells were identified by flow cytometry using monoclonal antibody and intracellular IL-17A staining. Th17 cells were defined as CD3+CD4+CD196+IL-17Aic+. The analysis involved anthropometric and metabolic parameters measured at baseline and three months after the change of lifestyle and diet. We evaluated the relationship between metabolic parameters and Th17 cells. Results In overweight and obese children we found significantly higher Th17 cells percentage compared to normal weight controls (median 0.097% (0.044 - 0.289) vs 0.041% (0.023 - 0.099), p = 0.048). The percentage of Th17 cells decreased statistically significantly in children who reduced weight after the intervention (0.210% (0.143 - 0.315) vs 0.039% (0.028 - 0.106), p = 0.004). In this group we also noticed statistically significant reduction of TC and LDL-C concentration (p = 0.01, p = 0.04, respectively). Conclusions Obesity in children is associated with increased percentage of peripheral Th17 cells. Weight reduction leads to significant decrease of circulating Th17 cells and improvement of lipid parameters. This significant reduction of proinflammatory Th17 cells is a promising finding suggesting that obesity-induced inflammation in children could be relatively easily reversible.